Cost‐utility of osteoarticular allograft versus endoprosthetic reconstruction for primary bone sarcoma of the knee: A markov analysis. Issue 3 (20th January 2017) - Wilson, Robert J.; Sulieman, Lina M.; VanHouten, Jacob P.; Halpern, Jennifer L.; Schwartz, Herbert S.; Devin, Clinton J.; Holt, Ginger E.
Abstract : BACKGROUND: The most cost‐effective reconstruction after resection of bone sarcoma is unknown. The goal of this study was to compare the cost effectiveness of osteoarticular allograft to endoprosthetic reconstruction of the proximal tibia or distal femur. METHODS: A Markov model was used. Revision and complication rates were taken from existing studies. Costs were based on Medicare reimbursement rates and implant prices. Health‐state utilities were derived from the Health Utilities Index 3 survey with additional assumptions. Incremental cost‐effectiveness ratios (ICER) were used with less than $100 000 per quality‐adjusted life year (QALY) considered cost‐effective. Sensitivity analyses were performed for comparison over a range of costs, utilities, complication rates, and revisions rates. RESULTS: Osteoarticular allografts, and a 30% price‐discounted endoprosthesis were cost‐effective with ICERs of $92.59 and $6 114.77. One‐way sensitivity analysis revealed discounted endoprostheses were favored if allografts cost over $21 900 or endoprostheses cost less than $51 900. Allograft reconstruction was favored over discounted endoprosthetic reconstruction if the allograft complication rate was less than 1.3%. Allografts were more cost‐effective than full‐price endoprostheses. CONCLUSIONS: Osteoarticular allografts and price‐discounted endoprosthetic reconstructions are cost‐effective. Sensitivity analysis, using plausible complication and revision rates, favored the use of discounted endoprostheses over allografts. Allografts are more cost‐effective than full‐price endoprostheses.